New Nonlocal Biological Effect: A Preliminary Research - Hu, Huping; Wu, Maoxin (NeuroQuantology, 2012)
We report here our experimental findings of new nonlocal biological effect measured objectively and quantitatively under blind conditions. The method used includes the steps of providing two parts of quantum-entangled medium, applying one part to a biological system such as a human, contacting the other part with a desired substance such as a medication, and detecting change of a biological parameter with a detecting device. Using this method, we have found that after consumption by a test subject of one part of the quantum entangled water, the subject's heart rate was non-locally increased under blind conditions by adding to the second part of the quantum-entangled water an over-the-counter medication Primatene which contains the heart stimulant ephedrine. The said increase of heart rate is measurable with a heart rate monitor, statistically significant and consistently reproducible. NeuroQuantology | September 2012 | Volume 10 | Issue 3 | Page 462-467